1994
DOI: 10.1161/01.atv.14.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasma HDL cholesterol and subfraction distribution by genetic and environmental factors. Associations between the TaqI B RFLP in the CETP gene and smoking and obesity.

Abstract: This study investigated in a healthy population (n=220) the association of the Taql B restriction fragment length polymorphism (RFLP) in the cholesteryl ester transfer protein (CETP) gene with plasma high-density lipoprotein (HDL) cholesterol concentration and subfraction distribution. A raised HDL cholesterol level was found in B2B2 homozygotes (B2 cutting site absent) and was associated specifically with a 45% increase in HDL 2 compared with B1B1 homozygotes (B1B1, 77±39 mg/100 mL, mean±SD; B2B2, 112±59 mg/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

31
135
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 33 publications
31
135
1
4
Order By: Relevance
“…Our finding that only 'never smokers' had a significant association of HDL-cholesterol levels with the B1 allele is in line with other studies. 4,5,16 Despite a more favorable baseline HDL-cholesterol, our patients with the B2B2 genotype had a higher event risk and a poor event-free survival, compared to carriers of the B1 allele. This finding is not in line with other studies that assessed cardiovascular event risks according to this polymorphism, and found that subjects with a B2 allele were more protected.…”
Section: Discussionmentioning
confidence: 62%
“…Our finding that only 'never smokers' had a significant association of HDL-cholesterol levels with the B1 allele is in line with other studies. 4,5,16 Despite a more favorable baseline HDL-cholesterol, our patients with the B2B2 genotype had a higher event risk and a poor event-free survival, compared to carriers of the B1 allele. This finding is not in line with other studies that assessed cardiovascular event risks according to this polymorphism, and found that subjects with a B2 allele were more protected.…”
Section: Discussionmentioning
confidence: 62%
“…Several previous studies have demonstrated such associations for HDL-C, specifically with SNP4 (TaqIB). [3][4][5]8,[35][36][37] In some reports, the association was seen only in subgroups, such as ex-and nonsmokers, 38 or in women, but not in men. 39 Alhough we could not replicate the association of an increased baseline HDL-C in the presence of the mutant B2 allele of SNP4, the strong stepwise decrease in CETP mass and activity associated with the number of B2 alleles of SNP4 clearly underlines such an expected effect on HDL-C. With respect to SNP 7 (A373P) and SNP8 (R451Q), the Copenhagen City Heart Study found a decrease in HDL-C and ApoA1 in carriers of the mutant allele, both in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the difference between the B2B2 group and the B1B1 group was greater among subjects with a high alcohol intake. Furthermore, Freeman and colleagues 7 reported that B2B2 homozygotes had signi®cantly higher plasma HDL-chol concentrations than B1B1 homozygotes when subjects were relatively lean but this difference was attenuated when subjects in the upper tertile of BMI (26.2 ± 40.4 kgam 2 ) were compared. Taken together, these results reinforce the notion that environmental factors may exert more in¯uence on plasma HDL-chol concentrations in B2 than in B1 carriers.…”
Section: Discussionmentioning
confidence: 99%